Revealing the structure of light pseudoscalar mesons at the electron–ion collider. (25th May 2021) - Arrington, J; Gayoso, C Ayerbe; Barry, P C; Berdnikov, V; Binosi, D; Chang, L; Diefenthaler, M; Ding, M; Ent, R; Frederico, T; Furletova, Y; Hobbs, T J; et al.
Abstract: The questions of how the bulk of the Universe's visible mass emerges and how it is manifest in the existence and properties of hadrons are profound, and probe the heart of strongly interacting matter. Paradoxically, the lightest pseudoscalar mesons appear to be key to a further understanding of the emergent mass and structure mechanisms. These mesons, namely, the pion and kaon, are the Nambu–Goldstone boson modes of quantum chromodynamics (QCD). Unravelling their partonic structure and the interplay between emergent and Higgs-boson mass mechanisms is a common goal of three interdependent approaches—continuum QCD phenomenology, lattice-regularised QCD, and the global analysis of parton distributions—linked to experimental measurements of hadron structure. Experimentally, the anticipated electron–ion collider will enable a revolution in our ability to study pion and kaon structures, accessed by scattering from the 'meson cloud' of the proton through the Sullivan process. With the goal of enabling a suite of measurements that can address these questions, we examine key reactions that identify the critical detector-system requirements needed to map tagged pion and kaon cross-sections over a wide range of kinematics. The excellent prospects for extracting pion structural, functional, and form-factor data are outlined, and similar prospects for kaon structures are discussed in the context of a worldwide programme. The successful completion of the programme outlined herein will deliver deep, far-reaching insights into the emergence of pions and kaons, their properties, and their role as QCD's Goldstone boson modes.